Association Between Metformin Use and the Risk, Prognosis of Gynecologic Cancer - Yao, Kui; Zheng, Heng; Li, Tao (Frontiers in Oncology, 2022)
Background For gynecological cancer patients, the beneficial effect of metformin use remains controversial due to inconsistent results of published articles. By conducting a meta-analysis, we aimed to evaluate the effect of metformin in reducing the risk and improving the survival of gynecological cancer among women with diabetes mellitus (DM). Methods Articles exploring association between metformin use and the risk, as well as prognosis of gynecologic cancer in DM, were searched in the databases: PubMed, Web of Science, SCOPUS, EMBASE, EBSCO, and PROQUEST. Articles were published before May 2022. All the studies were conducted using STATA 12.0 software. Results The meta-analysis showed no significant association between metformin use and risk of gynecologic cancer in DM with a random effects model [odds ratio (ORs)/relative risk (RR) = 0.91, 95% confidence intervals (CI) 0.77 to 1.08, I2 = 84.2%, p < 0.001]. Metformin use was associated with reduced overall survival (OS) and progression-free survival (PFS) of gynecologic cancer in DM with random effects models [OS: hazard ratio (HR) = 0.60, 95% CI 0.49–0.74, I2 = 55.2%, p = 0.002; PFS: HR = 0.55, 95% CI 0.33–0.91, I2 = 69.1%, p = 0.006], whereas no significant association was showed between metformin use and recurrence-free survival (RFS), as well as cancer-specific survival (CSS) of gynecologic cancer in DM with random effects models (RFS: HR = 0.60, 95% CI 0.30–1.18, I2 = 73.7%, p = 0.010; CSS: HR = 0.78, 95% CI 0.43–1.41, I2 = 72.4%, p = 0.013). Conclusions In conclusion, this meta-analysis indicated that metformin may be a useful adjuvant agent for gynecological cancer with DM, especially for patients with ovarian cancer and endometrial cancer.